Impact of sedimentation on evolution of accretionary wedges: Insights from high‐resolution thermomechanical modeling. Issue 12 (9th December 2016) - Mannu, Utsav; Ueda, Kosuke; Willett, Sean D.; Gerya, Taras V.; Strasser, Michael
Abstract: Syntectonic sedimentation history is a potential cause of differentiated accretionary wedge structures along the subduction margin. Recent efforts to model the role of sedimentation on wedge evolution have highlighted the importance of spatiotemporal history of sedimentation on the evolution of the wedge. Moreover, reconstruction of deformation history of the accretionary wedges using reflection seismic and borehole data has further substantiated the impact of sedimentation on wedge evolution. We conduct several numerical experiments using a high‐resolution dynamic 2‐D thermomechanical plate subduction model to systematically investigate and quantify different effects of sedimentation on accretionary wedge evolution. Models with sedimentation suggest migration of deformation to parts of the wedge lying outside the sedimentation zone leading to emergence/reactivation of out‐of‐sequence thrusts (OOSTs). Frequency and length of new thrust sheets are correlated with sedimentation in the trench. Models undergo a transition period of 1.5 Myr following the onset of sedimentation, after which they continue to grow under a new steady state. Stabilization of the wedge and increased load on the oceanic plate due to sedimentation create conditions in which smaller wedge‐top basins combine to form a large and flat forearc basin. Last but not the least, emergence of OOST in models of accretionary wedges undergoing sedimentation provides important insights in to evolution of potentially tsunamigenic OOSTs like the Megasplay Fault seaward of the Kumano forearc basin. Key Points: Accretionary wedge evolution during syntectonic sedimentation Out‐of‐sequence fault activity in accretionary wedge Temporal variation in Megasplay Fault activity in the Nankai Trough